Technological trends in the energy sector: challenges and threats - Stennikov Valerii; Bayar Bat-Erdene (E3S Web of Conferences, 2023)
The global trends taking place within the framework of the change of the technological way of life have largely determined the modern transformations taking place in the energy sector. These transformations have become the result of the challenges that have manifested themselves in recent years, and which have already acquired a large-scale character in many ways. They are associated with the rapid development of carbon-free, nature-like energy generation technologies based on renewable energy sources, distributed energy generation, the growth of consumer activity in regulating their demand, intellectualization, digitalization, decarbonization, integration and other processes taking place in the energy sector. These processes are objective and do not depend on conjunctural, political or any other preferences. In these conditions, the most important task of the present and future development and functioning of energy systems and the fuel and energy complex as a whole of the energy sector is to preserve the stability of their functioning and stable operation, ensuring socio-economic growth and energy security of the country.